Bridging the Gap : Aligning Teachers’ Pedagogical Beliefs with Learners’ Preferences of English Language Learning in The Adaptive Learning Era - Assis Hornay, Priscilla Maria; Talok, Damianus; Erom, Kletus (Jurnal Paedagogy, 2024)
This study aims to investigate the differing viewpoints of teachers and students regarding classroom participation, material delivery, teaching media, and assessment methods in the adaptive learning era. The study employs quantitative method, which involves the systematic collection and analysis of numerical data through statistical techniques. This study includes 10 teachers and 50 EFL undergraduate students from two universities in Indonesia, using a Likert scale questionnaire to collect data on various aspects of English language learning. The data were analysed using a t-test to find the mean, standards deviation, and p value of the responses in order to ascertained significant differences between the teachers and the students. The results reveal significant disparities between teachers’ and students’ perceptions across different dimensions of learning. While teachers prioritize delivery strategies and assessment methods, students focus more on delivery modes and traditional assessment types. However, both groups acknowledge the importance of autonomous learning and the effectiveness of diverse teaching media in enhancing engagement and motivation. The findings underscore the need for a balanced approach to learning that integrates both teacher preferences and student needs. Ultimately, understanding and addressing these discrepancies is essential for promoting meaningful and inclusive educational experiences in the adaptive learning era.